KONSEP BUDOO DALAM SENI BELA DIRI YANG BERAKAR DARI SENI BELA DIRI SAMURAI - , SARWI HENDAH K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Japan is known as a country which has many developing martial arts since the time of samurai. It was not only practiced by the Japanese, but also by people around the world. The martial art of samurai itself, which developed in Edo period had many influences from the works of Zen Buddhism tenets. It taught budoo as a concept in samurai meditation, so that the samurai were able to to find composure within. Budoo was a philosophy in martial arts which emphasized that any martial art aims to create peace for itâs practitioner and the environment. Martial arts which contain the budoo philosophy were not intent on getting victory from the fight but more to practice self development for the practitioner. The objective of this paper is to understand the relevance between budoo and the Zen tenets, and budooâs role in martial arts which emanated from samurai martial arts such as budoo in hakama, kendoo, iaidoo, juudoo, aikidoo, kyuudoo and naginata. This paper uses library methods to search for resources relevant to the whole theme.